A High Resolution Pitch Detection Algorithm Based on AMDF and ACF (Journal of Scientific Research, 2009)
This paper proposes a noise robust high resolution pitch detection algorithm based on AMDF and ACF. The falling trend of AMDF is eliminated by an alignment technique, and AMDF and ACF are combined to take the advantage of their complementary nature. These two functions are combined by multiplication and addition over several band pass filters to enhance important candidates and suppress less important candidates. Then using a sophisticated weight assignment procedure, the candidate with the highest weight is selected as pitch. The proposed method is evaluated on different colored noisy speech at different intensity. Experimental result shows noise robustness of the proposed method in varied environments. Keywords: AMDF; ACM; Pitch; Voice activity detection (VAD). © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i3.2569             J. Sci. Res. 1 (3), 508-515 (2009)